Hydrogeophysical assessment of some parts of Anambra basin, Nigeria - Chinwuko, Augustine; Anakwuba, Emmanuel; Nwokeabia, Nkechi; Onyekwelu, Clement (International Journal of Advanced Geosciences, 2014)
An electrical resistivity investigation has been carried out in thirteen communities within the Anambra Basin in order to determine the depth to the water table and groundwater flow in the area. Vertical electrical sounding (VES) curves were obtained across the area using the Schlumberger configuration. Both manual and computer interpretations of the resistivity data show basically three to five geo-electric units within the study area. The lowermost layer with the resistivity range of 144 - 1500 Ohm-m and depth of 14.9 – 166.41 m represents the aquifer. The water table map indicates multi flow direction and correlates favourably with the topography of the area. It was observed that the hydraulic conductivity obtained ranges from 6.67 x 10-4 to 6.944 x 10-3 m/day while the transmissivity ranges from 0.048 to 0.590 m2/day within the study area. Keywords: Groundwater, Resistivity Survey, Aquifer, Exploration, Schlumberger, Sounding.